PENGARUH KEBIASAAN BERBICARA BAHASA INGGRIS DAN MOTIVASI SISWA TERHADAP PRESTASI BELAJAR BAHASA INGGRIS SISWA - Dede Irawan (Faktor Jurnal Ilmiah Kependidikan, 2016)
Abstrak:The purpose of this research was determine the effect of  english habits and students motivation toward students achievement, the method used was a survey method  with corelation and regression analysis that conect the data showing english habits and students motivation were obtained trough a questionare prepared by the researcher, which measure thing related to the above two things. Mainwile data students achievment obtained from documents at the scholl, this is the result of general test final smester of the scholl year 2014/2015. The result of  the effect English Habit and student motivation toward  Student achievments corelation coeficient obtained for 2525,826  and  98,9% the coefficient of determnation regresion lien equation Y =  19,628 + 0,840X1 + 0,060X2. With tthe result f of regrssion significant obtained fh =2525,826with sig =  0,000 < 0,05Trough the analysis of the test shows that correaltion ceofficient and the regression ceoficient is significant, There are effect of  english habits and student motivation toward student Achievments. Key Words : English habit, student motivation, students achievment